A Review of Internet of Things (IoT) in Construction Industry: Building a Better Future - Katiyar, Ankit; Kumar, Pradeep (International Journal of Advanced Science Computing and Engineering, 2021)
Construction companies today are aiming for the finest technologies to achieve their targets in minimum cost possible along with a high level of security and safety. Construction companies are focusing more on the benefits of internet in their projects in order to improve processes, reduce waste and optimally utilize their resources and Internet of Things (IoT) is making it possible in a much more efficient way than thought of. IoT has now become the newest of the technology that is being used in the construction industry. IoT is basically the network of physical objects—buildings, vehicles, devices and other objects fixed with sensors, software, electronics and internet connectivity which aids these objects to collect, store and exchange data. This paper aims to improve the understanding of the importance of IoT and its implementation in the construction industry. The paper presents the compiled study of the works done by various researchers in which IoT can be used in the construction industry. The findings of their work have been discussed in this paper and future scope of work regarding the usage of IoT in different fields have been identified.